Electrosynthesis of Quinoxalines via Intermolecular Cyclization/Dehydrogenation of Ketones with o-Phenylenediamines - Tao, Yi; Zhang, Jiahui; Hu, Yangyang; Liu, Huiying; Sun, Jingwen; Liu, Lei (Synlett, 2024)
In this study, we proposed a novel electrochemical dehydrogenative synthetic method for preparing 2-substituted quinoxalines by intermolecular cyclization of aryl alkyl ketones and o-phenylenediamines. This method gave various quinoxalines in yields ranging from 35% to 71%. This novel protocol employs mild reaction conditions and offers moderate to excellent yields, a wide substrate scope, and broad functional-group compatibility. Furthermore, a late-stage functionalization and the wide substrate scope demonstrated the synthetic utility of this protocol.
Keywords: quinoxalines; electrochemistry; cyclization; green chemistry; dehydrogenation